Performance based structural fire safety concept for industrial buildings: strength and stability - Yolaçan, Taygun Fırat. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
The aim of this thesis is to investigate re characteristics and re induced structural performance of large scale industrial buildings to draw conclusions for a better and more robust sustainable structural design for re. According to National Fire Protection Association, an estimated average of 37.000 res at industrial buildings is reported in the U.S. during 2015. The structural re performance of ve di erent steel framed industrial buildings are investigated by conducting thermo-mechanical analysis in nite element software. The three-dimensional models of the buildings consist of structural members (column, beams, purlins, cross diagonals and tie-beams) and rigid connections between these members. To simulate the collapse of the buildings, an implicit dynamic analysis technique is employed. In addition, a simpli ed methodology is developed in order to investigate the thermo-mechanical behavior of composite oor systems. This methodology is implemented into Matlab. Realistic re scenarios are used for the thermo-mechanical analyses of the buildings. From strength and stability point of view, it is observed that re performance of isolated structural members is signi cantly di erent than the re performance of the members within a structural system. According to the analyses, the most severe conditions are observed in the regions where pre- ashover localized re is subjected and only two of the ve buildings satisfy the required structural re performance assessment. Adding a reinforced concrete slab to steel framed oor systems signi cantly reduces the span de ections during re due to catenary action in the slab. It is anticipated that the data collected in this thesis will lead to better understanding the re induced collapse mechanisms of industrial buildings.
Keywords: Fire prevention.; Factories -- Design and construction.